En - ALFIYAN WAHYU WICAKSONO; IMAM AGUS FAISOL (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
This study aims to examine the effect of the current ratio, debt to asset ratio, return on assets and tobin's q in influencing the incidence of financial distress in hotel sector companies affected by the COVID-19 pandemic. The data used in this study is secondary data obtained from the company's financial statements in 2020 - 2021. The object of this research is the hotel sector company which is listed on the Indonesia Stock Exchange and is included in the category of the Sharia Securities List. This study uses a purposive sampling method in determining the research sample, then obtained 8 companies with a total of 56 financial reports from the first quarter of 2020 to the third quarter of 2021. The hypothesis testing used is panel data regression with a significance level of 5%. The results of this study are showing that return on assets have no effect on financial distress. Meanwhile, the current ratio, debt to asset ratio, and Tobin's q have an effect on financial distress.